A method for preparing a biological antibacterial adhesive and application of the obtained adhesive

By adjusting the ratio of acid enzymatic hydrolysates and cationic polymers, the oxygen transmittance of biological antibacterial adhesives is improved, and the problem of low oxygen transmittance in the prior art is solved, and the effect of antibacterial, promoting tissue growth and improving mechanical properties is achieved.

CN118662684BActive Publication Date: 2025-04-25EXCELLENCE MEDICAL TECH SUZHOU CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410825517.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-25
Publication Date
2025-04-25
Estimated Expiration
2044-06-25

AI Technical Summary

Technical Problem

The existing bioadhesiveness of oxygen after implantation of humans affects the growth of cells and tissues around the material, and the use of cationic polymers reduces oxygen transmittance.

Method used

By adjusting the ratio of component A1 and component A2, using specific acid enzymatic hydrolysates and cationic polymers, the adhesive formation process of the binder is controlled to improve oxygen transmittance.

Benefits of technology

It realizes that while maintaining the antibacterial effect, the bioantibacterial adhesive improves oxygen transmittance, promotes tissue growth and wound healing, and improves the mechanical properties and adhesive properties of the adhesive.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
Patent Text Reader

Abstract

The present invention relates to a preparation method of a biological antibacterial adhesive and the application of the obtained adhesive. By controlling the weight ratio of component A1, component A2 and water (5-9): 1: (10-1000) in step S1, especially the ratio between component A1 and component A2, and using specific component A1 and component A2, that is, component A1 is an acidic enzymatic hydrolysate, in which the substance with an absolute molecular weight of 90-110 kDa accounts for 20-40wt%, the substance with an absolute molecular weight of 40-60 kDa accounts for 20-40wt%, and component A2 is a cationic polymer with a polymerization degree of 9-32, and the polymer unit of the cationic polymer contains two nitrogen atoms, so that the obtained adhesive has an antibacterial effect and good oxygen permeability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of medical materials, and in particular relates to a preparation method of a biological antibacterial adhesive and application of the obtained adhesive. Background Art

[0002] Chemically synthesized polymers as adhesives have good adhesion and mechanical strength, but they have certain biocompatibility issues, and once the material is detached from the tissue after implantation, it will cause damage to the tissue. Therefore, the commercialization of bioadhesives has received widespread attention.

[0003] Patent No. CN114712550B provides an injectable rapid hemostatic hydrogel adhesive and a preparation method and application thereof. The product obtained by reacting polypropylene, chitosan, sodium alginate and calcium chloride can effectively stop bleeding at a defect with a diameter of 2 mm within 10 seconds. Patent No. CN110484184B discloses a hydrogel adhesive and its application and application thereof. The reaction is carried out using polyethylene glycol derivatives and endogenous organic dopamine to improve the adhesion of the adhesive in a water environment. Patent No. CN115433318A discloses a hydrogel bioadhesive material and a preparation method thereof. The material is prepared using a benzimidazole-modified hydrophilic polymer and cyclodextrin, so that the adhesion of the hydrogel changes with the acidity of the environment.

[0004] None of the above prior arts mentions the oxygen permeability of adhesives. In the practice of using biological adhesives for human implants, people often pay great attention to their biocompatibility, but oxygen permeability is often ignored. Oxygen permeability not only affects the growth of cells and tissues around the material, thereby affecting the healing ability of the wound surface, but also, since the oxygen permeability coefficient is generally proportional to the water content, and the water content is closely related to the mechanical properties of the material, it can be seen that oxygen permeability also affects the mechanical properties of the material. Summary of the invention

[0005] In order to solve the above problems and improve the oxygen permeability of the adhesive, the first aspect of the present invention provides a method for preparing a biological antibacterial adhesive, and the preparation method is as follows:

[0006] S1. Preparation of component A: Component A1, component A2 and water are mixed in a weight ratio of (0.1-10):1:(10-1000), and freeze-dried to obtain component A;

[0007] S2. Component A is dissolved in a buffer solution, wherein the content of component A in the buffer solution is 10-16wt%;

[0008] S3. The modified hydrophilic polymer is dissolved in a buffer solution, wherein the content of the modified hydrophilic polymer in the buffer solution is 10-16 wt %;

[0009] S4. The buffer solution of component A obtained in step S2 and the buffer solution of the modified hydrophilic polymer obtained in step S3 are mixed in a weight ratio of (0.8-1.5):1 to form a gel.

[0010] Preferably, S1. Preparation of component A: Component A1, component A2 and water are mixed in a weight ratio of (2-9):1:(10-1000), and then freeze-dried to obtain component A.

[0011] Further preferably, S1. Preparation of component A: Component A1, component A2 and water are mixed in a weight ratio of (5-9):1:(10-1000), and then freeze-dried to obtain component A.

[0012] More preferably, S1. Preparation of component A: Component A1, component A2 and water are mixed in a weight ratio of (7-9):1:(10-1000), and then freeze-dried to obtain component A.

[0013] In the preparation process of component A, water only plays the role of dispersing component A1 and component A2, so that component A1 and component A2 can be well mixed.

[0014] As a preferred embodiment, the component A1 is an acidic enzymatic hydrolysate, in which substances with an absolute molecular weight of 90-110 kDa account for 20-40 wt%, and substances with an absolute molecular weight of 40-60 kDa account for 20-40 wt%.

[0015] In the present invention, the absolute molecular weight distribution of the acidic enzymatic hydrolysate is determined by laser light scattering and gel permeation chromatography.

[0016] Preferably, the component A1 is an acidic enzymatic hydrolysate, in which substances with an absolute molecular weight of 95-105 kDa account for 20-40 wt%, and substances with an absolute molecular weight of 45-55 kDa account for 20-40 wt%.

[0017] Preferably, the component A1 is an acidic enzymatic hydrolysate, in which substances with an absolute molecular weight of 100 kDa account for 20-40 wt%, and substances with an absolute molecular weight of 50 kDa account for 20-40 wt%.

[0018] Further preferably, the component A1 is an acidic enzymatic hydrolysate, in which substances with an absolute molecular weight of 95-105 kDa account for 22-35 wt %, and substances with an absolute molecular weight of 45-55 kDa account for 25-38 wt %.

[0019] Preferably, the component A1 is an acidic enzymatic hydrolysate, in which substances with an absolute molecular weight of 95-105 kDa account for 23-34 wt %, and substances with an absolute molecular weight of 45-55 kDa account for 27-36 wt %.

[0020] Preferably, the component A1 is an acidic enzymatic hydrolysate, in which substances with an absolute molecular weight of 100 kDa account for 22-35 wt %, and substances with an absolute molecular weight of 50 kDa account for 25-38 wt %.

[0021] As a preferred embodiment, the preparation method of the acidic enzymatic hydrolysate is: 0.05-0.8 mmol / mL of a protease aqueous solution is adjusted to an acidic pH, decellularized matrix particles are added so that the weight proportion of the decellularized matrix particles in the protease aqueous solution is 1-20wt%, the solution is allowed to stand and then filtered, the filtrate is taken, and the filtrate is freeze-dried to obtain the product.

[0022] The protease is not particularly limited, and may be trypsin, pepsin, or the like.

[0023] Preferably, the weight proportion of the decellularized matrix particles in the aqueous solution of protease is 1-15 wt %.

[0024] Preferably, the weight proportion of the decellularized matrix particles in the aqueous solution of protease is 1-10 wt %.

[0025] As a preferred embodiment, the decellularized matrix particles are obtained by physically crushing the decellularized matrix material, and the diameter of the decellularized matrix particles is 50-350 meshes.

[0026] Preferably, the decellularized matrix particles are prepared by physically pulverizing the decellularized matrix material.

[0027] Preferably, the acellular matrix material is at least one of small intestinal submucosa, porcine bladder basement membrane, peritoneum, pericardium, and dermis.

[0028] In the present invention, the small intestinal submucosa and porcine bladder basement membrane were purchased from Zhuoruan Medical Technology (Suzhou) Co., Ltd.

[0029] As a preferred embodiment, the component A2 is a cationic polymer, and the degree of polymerization of the cationic polymer is 9-32.

[0030] Preferably, the degree of polymerization of the cationic polymer is 9-17 or 25-30.

[0031] Preferably, the cationic polymer is selected from one of polylysine, polyarginine, polyleucine and polythreonine.

[0032] Further preferred cationic polymers are polylysine or polyarginine.

[0033] As a preferred embodiment, the cationic polymer contains two nitrogen atoms in the polymer unit.

[0034] Preferably, the cationic polymer is polylysine. The polymer unit lysine of polylysine contains two nitrogen atoms.

[0035] The structural characteristics of cationic polymers make them antibacterial and not easy to induce bacterial resistance. Therefore, the inventors added cationic polymers to the adhesive to make the adhesive have antibacterial effects. However, the inventors found that cationic polymers would reduce the oxygen permeability of the adhesive. The insertion of the polymer network into the pores of the decellularized matrix reduced the adhesive's ability to dissolve and diffuse oxygen, affecting the growth of cells and tissues around the material, thereby affecting the healing ability of the wound. Especially for surface wounds, the influence of oxygen permeability is very important. To this end, the inventors have found through thinking and a large number of experiments that by controlling the weight ratio of component A1, component A2 and water (5-9): 1: (10-1000) in step S1, especially the ratio between component A1 and component A2, and using specific components A1 and A2, that is, component A1 is an acid hydrolyzate, in which the substance with an absolute molecular weight of 90-110 kDa accounts for 20-40 wt%, and the substance with an absolute molecular weight of 40-60 kDa accounts for 20-40 wt%, and component A2 is a cationic polymer with a degree of polymerization of 9-32, and the polymer unit of the cationic polymer contains two The nitrogen atom can effectively overcome the above problems, so that the prepared adhesive has an antibacterial effect and a good oxygen permeability. Unexpectedly, the mechanical properties and adhesive properties of the adhesive are improved, especially the stability of the adhesive properties. The applicant speculates that the specific regulation of components A1 and A2 in the present invention affects the gaps when the adhesive is gelled, and the thermal motion of the water molecules of free water and bound water and the diffusion filtration of the adhesive gel cross-linked network are all affected. At the same time, the electrostatic effect of the complex micelles formed by steps S1-S4 further affects its fluidity, which again reacts to affect the above movement. Further, the present invention uses dendritic cationic polymers and linear cationic polymers, both of which will produce improvements in mechanical properties, adhesive properties and oxygen permeability, but the improvement effect of dendritic cationic polymers is particularly significant, which may be due to its greater contribution to the improvement of the adhesive cross-linked network.

[0036] As a preferred embodiment, the relative molecular weight of the modified hydrophilic polymer is 1000-5000 Da.

[0037] Preferably, the modified hydrophilic polymer is four-arm-polyethylene glycol-succinimidyl glutaric acid (4arm-PEG-SG).

[0038] Preferably, in steps S2 and S3, the buffer solution is 2-15 times of PBS buffer.

[0039] Further preferably, the buffer solution is 10×PBS buffer (ie, 10 times of PBS buffer) or 5×PBS (ie, 5 times of PBS buffer) buffer.

[0040] In the present invention, the applicant also found that the concentration of the buffer solution is not randomly selected and should not be too high or too low. If the concentration of the buffer solution is too high, the excessively concentrated sodium salt, potassium salt, etc. will affect the cross-linking network of the adhesive and affect the gelling effect; while the buffer solution with too low a concentration will also reduce the mechanical properties and bonding effect of the adhesive. The inventor speculates that this may be because if the salt ions in the system are too low, the hydrophobic effect inside the decellularized matrix particles and the cationic polymer will be enhanced, causing aggregation.

[0041] As a preferred embodiment, S4 is: the buffer solution of component A obtained in step S2 and the buffer solution of the modified hydrophilic polymer obtained in step S3 are mixed in a weight ratio of (0.9-1.3):1 to form a gel.

[0042] The second aspect of the present invention provides an adhesive prepared by the preparation method of the biological antibacterial adhesive.

[0043] The third aspect of the present invention provides an application of an adhesive to body surface wounds, abdominal wounds, pelvic wounds, lung occlusion and lung isolation.

[0044] Beneficial effects: Component A and the modified hydrophilic polymer in the present invention can be dispersed quickly and evenly, and while quickly forming gel, the stability and uniformity of the adhesive product obtained in dry and wet states are guaranteed; the obtained adhesive has an antibacterial effect and a good oxygen permeability, which is not only conducive to improving the biocompatibility of the material, but also provides a wet state through a continuous hydration effect, and due to the transport of cell nutrients, the tissue can better grow into the wound surface where the adhesive is used, maintaining the balance of the physiological environment. In addition, the mechanical properties and adhesive properties of the adhesive are improved, and the bonding effect is more stable and lasting. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 This is a diagram of the biological antibacterial adhesive prepared in Example 1 and pig skin with a similar tissue structure to that of the human body after being bonded for 60 minutes;

[0046] Figure 2This is a diagram of the biological antibacterial adhesive prepared in Comparative Example 1 and pig skin with a similar tissue structure to that of the human body after being bonded for 60 minutes. DETAILED DESCRIPTION

[0047] The materials in the examples are all commercially available, among which the porcine bladder basement membrane was purchased from Zhuoruan Medical Technology (Suzhou) Co., Ltd.

[0048] Example 1

[0049] This example provides a method for preparing a biological antibacterial adhesive, and the preparation method is as follows:

[0050] S1. Preparation of component A: Component A1, component A2 and water are mixed in a weight ratio of 9:1:200, and freeze-dried to obtain component A;

[0051] Component A1 is an acidic enzymatic hydrolysate, in which substances with an absolute molecular weight of 90-110 kDa account for 20-40 wt%, and substances with an absolute molecular weight of 40-60 kDa account for 20-40 wt%.

[0052] The preparation method of the acidic enzymatic hydrolysate is as follows: a 0.35 mmol / mL pepsin aqueous solution is adjusted to an acidic pH, decellularized matrix particles are added so that the weight proportion of the decellularized matrix particles in the protease aqueous solution is 10 wt %, the solution is allowed to stand for full reaction and then filtered, the filtrate is taken, and the filtrate is freeze-dried to obtain the product.

[0053] The decellularized matrix particles are prepared by physically crushing the decellularized matrix material with a physical crusher. The diameter of the decellularized matrix particles can be set by selecting the particle output parameters of the physical crusher. The decellularized matrix material is porcine bladder basement membrane, and the diameter of the decellularized matrix particles is 50-350 meshes.

[0054] Component A2 is a cationic polymer, and the cationic polymer is polylysine (purchased from Chenyuan Molecular, model D3-(NH2HCL) 16 , dendritic, degree of polymerization 16). The polymer unit lysine of polylysine contains two nitrogen atoms.

[0055] S2. Component A is dissolved in a buffer solution, wherein the content of component A in the buffer solution is 15wt%;

[0056] S3. The modified hydrophilic polymer is dissolved in a buffer solution, wherein the content of the modified hydrophilic polymer in the buffer solution is 15 wt %;

[0057] The modified hydrophilic polymer is four-arm-polyethylene glycol-succinimidyl glutaric acid (4arm-PEG-SG) (purchased from Shanghai Zhenzhun Biotechnology Co., Ltd., relative molecular weight 5000Da, model ZP-61507).

[0058] In steps S2 and S3, the buffer solution is 10× PBS buffer (purchased from Shanghai Zhen Biotechnology).

[0059] S4. The buffer solution of component A obtained in step S2 and the buffer solution of the modified hydrophilic polymer obtained in step S3 are mixed in a weight ratio of 1.2:1 to form a gel.

[0060] Example 2

[0061] This example provides a method for preparing a biological antibacterial adhesive. The difference from Example 1 is that in step S1, component A1, component A2 and water are mixed in a weight ratio of 5:1:200 and then freeze-dried to obtain component A; component A2 is a cationic polymer, and the cationic polymer is polylysine (purchased from Maidehao Chemical, model ε-polylysine, linear, degree of polymerization 26-30).

[0062] Comparative Example 1

[0063] This example provides a method for preparing a biological antibacterial adhesive. The difference from Example 1 is that in step S1, component A1, component A2 and water are mixed in a weight ratio of 15:1:200, and then freeze-dried to obtain component A.

[0064] Comparative Example 2

[0065] This example provides a method for preparing a biological antibacterial adhesive. The difference from Example 1 is that in step S1, component A1, component A2 and water are mixed in a weight ratio of 8:1:200 and then freeze-dried to obtain component A; component A2 is a cationic polymer, and the cationic polymer is polylysine (purchased from Chenyuan Molecular, model D2-(NH2HCL)8, dendritic, degree of polymerization 8).

[0066] Comparative Example 3

[0067] This example provides a method for preparing a biological antibacterial adhesive. The difference from Example 1 is that in step S1, component A1, component A2 and water are mixed in a weight ratio of 7:1:200, and then freeze-dried to obtain component A; component A2 is a cationic polymer, and the cationic polymer is polyarginine (purchased from NewPu Biotechnology, model number nine polyarginine, dendritic, degree of polymerization 9). The polymer unit arginine of polyarginine contains 4 nitrogen atoms.

[0068] Comparative Example 4

[0069] This example provides a method for preparing a biological antibacterial adhesive. The difference from Example 1 is that in steps S2 and S3, the buffer solution is 20×PBS buffer (purchased from Shanghai Zhen Biological).

[0070] Test Results

[0071] 1. Oxygen permeability: The oxygen permeability of the bio-antibacterial adhesives prepared by the preparation methods of Examples 1-2 and Comparative Examples 1-4 was tested according to GB / T 19789-2005. The results are shown in Table 1.

[0072] Table 1

[0073] Example <![CDATA[Oxygen transmission rate (cm 3 / (m 2 ·24 h))]]> Example 1 473 Example 2 515 Comparative Example 1 362 Comparative Example 2 314 Comparative Example 3 387 Comparative Example 4 425

[0074] Compared with Example 1, the oxygen permeability of the biological antibacterial adhesive obtained in Comparative Example 4 is greatly reduced. The inventors speculate that this may be due to the use of 20×PBS buffer in steps S2 and S3, which introduces too much salt into the system and affects the gelling effect of the adhesive.

[0075] 2. Mechanical strength: The bio-antibacterial adhesives obtained by the preparation methods of Examples 1-2 and Comparative Examples 1-4 were compressed to 50% in a universal testing machine at a compression rate of 20 mm / min for 10 cycles to test their compression strengths at 50%. The results are shown in Table 2.

[0076] Table 2

[0077] Example Compression strength (kPa) Example 1 59.2 Example 2 58.4 Comparative Example 1 36.7 Comparative Example 2 43.5 Comparative Example 3 64.3 Comparative Example 4 48.6

[0078] The mechanical properties of the adhesive itself, namely cohesion, is one of the decisive factors for the macroscopic bonding strength of the adhesive. The higher the compression strength, the greater the cohesion of the gel formed by the adhesive, which helps to improve its macroscopic bonding strength.

[0079] 3. Adhesion performance: Pigskin with a structure similar to human tissue was selected for the first lap-shear adhesion strength test. The test method refers to YY / T0729.1-2009. After the first test, the lap-shear adhesion strength stability test was performed, and the test results are shown in Table 3. The shear adhesion strength was tested 24 hours after the preparation of the glue, and the stability of the adhesion performance was evaluated by the difference before and after.

[0080] Table 3

[0081] Example Bond strength (kPa) Bond strength after 24 hours of preparation (kPa) Example 1 43 42 Example 2 48 50 Comparative Example 1 33 17 Comparative Example 2 39 35 Comparative Example 3 48 41 Comparative Example 4 37 35

[0082] 4. Adhesive sealing test: The bursting strength was measured on pig stomach tissue with reference to ASTM F2392-04, and certain adjustments were made according to the actual situation: fresh pig skin tissue was selected, fully cleaned, a small hole with a diameter of 3 mm was punched in the middle of the tissue, and it was placed on the bursting strength test device, and the biological antibacterial adhesive obtained by the preparation method of Examples 1-2 and Comparative Examples 1-4 (the buffer solution of component A and the buffer solution of the modified hydrophilic polymer obtained in step S3 were mixed and dripped at the small hole, with a total volume of 1 mL, mixed, and gelled) was placed on the small hole, and the bursting strength was measured after gelling, and physiological saline was passed into one end of the device by a peristaltic pump, and a pressure gauge was connected to the other end to measure the maximum water pressure that the small hole sealed with the adhesive could bear, and the results are shown in Table 4. As can be seen from Table 4, the bursting strengths of Examples 1-2 are 23.6 kPa and 22.4 kPa, respectively, which are much greater than the normal blood pressure of the human body (10-16 kPa), which shows that the adhesive of Examples 1-2 has good sealing performance.

[0083] Table 4

[0084] Example Burst strength (kPa) Example 1 23.6 Example 2 22.4 Comparative Example 1 16.8 Comparative Example 2 19.5 Comparative Example 3 24.3 Comparative Example 4 19.7

[0085] 5. Uniformity: Take the biological antibacterial adhesives obtained by the preparation methods of Examples 1-2 and Comparative Examples 1-4, take different parts of each adhesive to test the absorbance at a total of 10 points, and calculate the relative standard deviation RSD. The smaller the RSD, the higher the uniformity of the adhesive. The results are shown in Table 5.

[0086] Table 5

[0087] Example RSD(%) Example 1 1.22 Example 2 2.35 Comparative Example 1 6.04 Comparative Example 2 4.83 Comparative Example 3 4.46 Comparative Example 4 2.54

Claims

1. A method for preparing a biological antibacterial adhesive, characterized in that: The preparation method is as follows: S1. Preparation of component A: Component A1, component A2 and water are mixed in a weight ratio of (0.1-10):1:(10-1000), and freeze-dried to obtain component A; the component A1 is an acidic enzymatic hydrolysate, in which substances with an absolute molecular weight of 90-110 kDa account for 20-40 wt%, and substances with an absolute molecular weight of 40-60 kDa account for 20-40 wt%; The preparation method of the acidic enzymatic hydrolysate is as follows: adjusting the pH of a 0.05-0.8 mmol / mL protease aqueous solution to an acidic pH, adding decellularized matrix particles so that the weight proportion of the decellularized matrix particles in the protease aqueous solution is 1-20 wt %, filtering after standing, taking the filtrate, and freeze-drying the filtrate to obtain the acidic enzymatic hydrolysate; The component A2 is a cationic polymer, the degree of polymerization of the cationic polymer is 9-32, and the polymer unit of the cationic polymer contains two nitrogen atoms; The cationic polymer is polylysine; S2. Component A is dissolved in a buffer solution, wherein the content of component A in the buffer solution is 10-16wt%; S3. The modified hydrophilic polymer is dissolved in a buffer solution, wherein the content of the modified hydrophilic polymer in the buffer solution is 10-16 wt %; the modified hydrophilic polymer is four-arm-polyethylene glycol-succinimidyl glutaric acid; In steps S2 and S3, the buffer solution is 2-15 times of PBS buffer; S4. The buffer solution of component A obtained in step S2 and the buffer solution of the modified hydrophilic polymer obtained in step S3 are mixed in a weight ratio of (0.8-1.5):1 to form a gel.

2. The method for preparing the biological antibacterial adhesive according to claim 1, characterized in that: The decellularized matrix particles are prepared by physically crushing the decellularized matrix material, and the diameter of the decellularized matrix particles is 50-350 meshes.

3. The method for preparing the biological antibacterial adhesive according to claim 1, characterized in that: The relative molecular weight of the modified hydrophilic polymer is 1000-5000Da.

4. The method for preparing the biological antibacterial adhesive according to claim 1, characterized in that: The step S4 is: mixing the buffer solution of component A obtained in step S2 and the buffer solution of the modified hydrophilic polymer obtained in step S3 in a weight ratio of (0.9-1.3):1 to form a gel.

5. An adhesive prepared according to the method for preparing a biological antibacterial adhesive according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • A hydrogel adhesive, its preparation method and application

    CN110484184B

  • Hydrogel biological adhesive material and preparation method thereof

    CN115433318A

  • Medical gel dressing as well as preparation method and application thereof

    CN116983466A

  • Biological adhesive and preparation method thereof

    CN117695434A